Cues that Matter: The Potential for black campaigns in the 2024 general election - Hasse Jubba; Henky Fernando; Yuniar Galuh Larasati; Umar Warfete (Khazanah Sosial, 2023)
Black campaigns that occurred in 2014 and 2019 also have the potential to emerge in the 2024 general elections in Indonesia. Not only does black campaigning have the potential to create public distrust of a fair electoral process, but it also has the potential to polarize society. This phenomenon has not been scientifically considered in previous studies. This study focuses on the question, "What is the potential for black campaigns that occurred in 2014 and 2019 to emerge in the 2024 general election in Indonesia?" This qualitative study investigates the forms and patterns of black campaign narratives disseminated through online media coverage. The findings of this study show that the black campaign that occurred in 2014 has the same pattern and narrative in 2019. Issues such as the involvement of the Indonesian Communist Party, Race, Human Rights, Radicalism, and Religion became issues that did not appear in the black campaign in the 2014 and 2019 general elections. The patterns and narratives of black campaigns that occurred in 2014 and 2019 can be used as references and preferences in looking at black campaign issues that have the potential to appear in the 2024 general elections. This study also recommends the importance of analyzing the factors that influence the emergence of black campaigns with the same patterns and narratives in 2014 and 2019 that have the potential to appear in the 2024 general elections in Indonesia.